Mental Health Disorders in Nurses During the COVID-19 Pandemic: Implications and Coping Strategies - Riedel, Brittney; Horen, Sydney R.; Reynolds, Allie; Hamidian Jahromi, Alireza (Frontiers in Public Health, 2021)
Nurses caring for patients who contract coronavirus disease 2019 (COVID-19) have experienced significant traumas in the form of increased workloads, negative patient outcomes, and less social support system access. Nurses should be provided with information regarding early detection, coping skills and treatment for anxiety, depression, post-traumatic stress syndrome (PTSS)/post-traumatic stress disorder (PTSD), and other mental health disorders. Early intervention is important as mental health disorders can cause dysfunction, internal suffering, and in the most extreme situations, lead to death if not properly cared for. Healthcare corporations should consider providing coverage for mental health treatment for employees who experience COVID-19 traumas. With the implementation of healthy coping skills and therapeutic intervention, nurses will be able to let go of the negative impacts that the COVID-19 pandemic has caused and reintegrate into their roles as caring and entrusted health care providers. The current paper evaluates the mental health disorders encountered by nurses in the COVID-19 era based on the current medical literature and aims to provide practical coping strategies.